Estimation of Population Variance Using Auxiliary Information - Misra, Peeyush Misra (IJRDO -JOURNAL OF MATHEMATICS, 2016)
A generalized estimator representing a class of estimators using auxiliary information in theform of mean and variance is proposed. The expression for bias and mean square error are foundand it is shown that the proposed generalized class of estimator is more efficient than few of theestimators available in the literature. An empirical study is also included as an illustration.